20 years Collaborative Governance and Action Research: Evaluation Process of the Regional Spatial Planning of Mappi Regency, Papua - Doddy Aditya Iskandar (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
This paper evaluates planners’ capacity to influence the plan-making process where it often involves actors and institutions with various interests. Relegating planners’ roles by providing mere technical inputs to those who seek advice would not alleviate spatial imbalance and unequal power structure embedded in the community. Planners should be reflexive and accountable, as it will lead them to aspire to a contested ideal rather than to simply optimize the current system in which they are in. Drawing from our experience in reviewing regional spatial plan of Kabupaten Mappi, providing an alternative approach to current development strategies would help balancing the local community’s power structure. Planners should master the politics of planning as it would help them influence the decision-making process.